Estimating bole wood specific gravity in trees of temperate forest communities of northern Durango, Mexico - Silva-Arredondo, Flor María; Návar-Cháidez, José de Jesús (Instituto de Ecología, A.C., 2016)
The objective of this research was to estimate basic wood specific gravity and its level of variation among biomass components of trees of several species of the genera Pinus and Quercus of northern Durango, Mexico. A total of 843 wood core sepecimens were taken at different heights and at different diameter sections from 113 trees. Fresh wood blocks of 2,5 cm x 2,5 cm x 2,5 cm were measured and once they were oven dried they were weighted to estimate the wood specific gravity. Results showed that the basic wood specific gravity was statistically different between biomass components along the diameter and height gradients (P > F = 0,0001) for trees of the genus Pinus unlike for trees of the genus Quercus. Mathematical evaluations show that wood cores for measuring the bole wood specific gravity must be taken at a height of 0,22H instead of the traditional height of 1,3 m at which it is conventionally evaluated.